Effect of Estrogen on Serum Total Cholesterol and Triglyceride Levels in postmenopausal women (Journal of Dhaka Medical College, 2017)
Background: Hyperlipidemia is a major risk factor for cardiovascular diseases in postmenopausal women. Increased incidence of cardiovascular diseases in postmenopausal women may be due to hyperlipidemia caused by lower level of estrogen hormone.Objectives: The study was carried out to observe the association of serum estrogen with total cholesterol (TC) and triglyceride (TG) levels in postmenopausal women.Methods: This cross sectional study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka, during the period of January to December 2011. A total of 90 females were selected from different areas of Dhaka city. Among them, 60 postmenopausal women with age ranging from 50 to 60 years were taken as study group and 30 apparently healthy premenopausal women with age ranging from 20 to 30 years were included as control group for comparison. The study parameters total cholesterol and triglyceride were estimated by enzymatic method in both groups. Serum estrogen level was estimated by Radioimmunoassay ( RIA) method in order to assess the hormonal level of both groups. Data was analyzed by Unpaired Students t- test and Pearsons correlation co-efficient (r) test as applicable.Results: In this study, the mean serum TC level was higher in postmenopausal women than those of premenopausal women and result was statistically significant. The level of mean serum TG was significantly (p